Several Questions about Gear Single Tooth Pulsating Bending Fatigue Test - Liu Ziqiang; Chen Liang; Wan Wenming (Jixie chuandong)
The methods of the tooth root bending fatigue test both at home and abroad are introduced,and several questions about single tooth pulsating test are explained and discussed,such as ensure the load distribution along tooth length direction,clamped tooth number and loading point position,the loading frequency and the tooth form factor,stress concentration factor and tooth root surface condition factor for calculation and so on.